Uncertainty about Rater Variance and Small Dimension Effects Impact Reliability in Supervisor Ratings. Issue 3 (8th August 2022) - Jackson, Duncan; Michaelides, George; Dewberry, Christopher; Jones, Amanda; Toms, Simon; Schwencke, Ben; Yang, Wei-Ning
ABSTRACT: We modeled the effects commonly described as defining the measurement structure of supervisor performance ratings. In doing so, we contribute to different theoretical perspectives, including components of the multifactor and mediated models of performance ratings. Across two reanalyzed samples (Sample 1, N ratees = 392, N raters = 244; Sample 2, N ratees = 342, N raters = 397), we found a structure primarily reflective of general (>27% of variance explained) and rater-related (>49%) effects, with relatively small performance dimension effects (between 1% and 11%). We drew on findings from the assessment center literature to approximate the proportion of rater variance that might theoretically contribute to reliability in performance ratings. We found that even moderate contributions of rater-related variance to reliability resulted in a sizable impact on reliability estimates, drawing them closer to accepted criteria.